Psalms old and new : exegesis, intertextuality, and hermeneutics - Witherington, Ben, III, 1951- (Fortress Press, 2017)
"Psalms in context and through the ages. Reading the Book of Psalms in its original context is the crucial prerequisite for reading its citation and use in later interpretation, including the New Testament writings, argues Ben Witherington III. Here, he offers pastors, teachers, and students an accessible commentary to the Psalms, as well as a reasoned consideration of how they were heard and read in early Christianity. By reading "forward and backward," Witherington advances the scholarly discussion of intertextuality and opens a new avenue for biblical theology. - Back cover."--Back cover.